Mehr Kooperation von Start-ups und Mittelstand als Chance für Digitalisierung und Innovationen; More cooperation between startups and SMEs as an opportunity for digital transformation and innovation - Klaus-Heiner Röhl; Barbara Engels (Wirtschaftsdienst, 2021)
Die Corona-Krise hat die Defizite Deutschlands in der Digitalisierung von Wirtschaft und Gesellschaft schlagartig offengelegt. Die Zusammenarbeit von etabliertem Mittelstand und innovativen Start-ups - oft mit digitalen Geschäftsmodellen - bietet dabei große Chancen für die Beteiligten und die Wirtschaft insgesamt. Auch könnte das demografiebedingt nachlassende Wachstumspotenzial der deutschen Wirtschaft steigen. – – The Coronavirus crisis clearly exposed Germany's deficits in the digitalisation of the economy and society. The cooperation between established SMEs and innovative start-ups offers considerable opportunities for the respective companies and the German economy. New business models can be adopted and innovative products can be jointly developed. In particular, the digitalisation of the 'German Mittelstand' could receive a boost through collaboration with digital start-ups. This could lead to an increase in the demographically induced declining growth potential of the German economy.
Keywords: L14; L23; L26; 330